2008
DOI: 10.1103/physreva.78.023619
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects in a guided-wave atom interferometer with millimeter-scale arm separation

Abstract: Abstract. Guided-wave atom interferometers measure interference effects using atoms held in a confining potential. In one common implementation, the confinement is primarily two-dimensional, and the atoms move along the nearly free dimension under the influence of an off-resonant standing wave laser beam. In this configuration, residual confinement along the nominally free axis can introduce a phase gradient to the atoms that limits the arm separation of the interferometer. We experimentally investigate this e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 21 publications
4
69
0
Order By: Relevance
“…This, as well as several other experiments [1,[14][15][16] on BEC-based atom interferometry, shows that condensates are good candidates for interferometric applications. BEC-based atom interferometers in Michelson geometry [1,17] and in Mach-Zehnder geometry [18,19] were realized recently.…”
Section: Introductionsupporting
confidence: 73%
“…This, as well as several other experiments [1,[14][15][16] on BEC-based atom interferometry, shows that condensates are good candidates for interferometric applications. BEC-based atom interferometers in Michelson geometry [1,17] and in Mach-Zehnder geometry [18,19] were realized recently.…”
Section: Introductionsupporting
confidence: 73%
“…We find a linearly reduced dephasing rate at reduced wave-packet displacements, indicating that the matter-wave dephasing is due to very weak potential variation along the waveguide in our setup. We have demonstrated phase stability for an interferometry sequence with total 043631-4 interrogation time exceeding 1 s. We also showed that a four-pulse interferometer can provide acceleration measurements with very long integration times that are insensitive to apparatus vibrations, though it is important to note that the sensitivity of the interferometer scheme we describe is compromised by the small wave-packet separations [10].…”
Section: Discussionmentioning
confidence: 94%
“…More recent experiments using Bose condensates [8] have shown that the external state coherence can be preserved for approximately 200 ms, where the decoherence is dominated by atom-atom interactions. Interferometry experiments using either condensed atoms in a weak trap or noncondensate atoms in a waveguide with precise angular alignments have been shown to have phase-stable interrogation times of ≈50 ms, where the dephasing is induced by inhomogeneities in the confining potential [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the probe pulse can be longer than the duration of the modulation echo. Small fluctuations in the trap frequency can be measured simultaneously with the phase shift and using thermal atoms avoids the critical timing needed when a BEC is used [16,18,21]. It may prove possible to measure the interference signal more than once in any given experiment.…”
Section: Introductionmentioning
confidence: 99%
“…A major difficulty with all trapped atom interferometers that use optical pulses is that the residual potential along the guide causes decoherence [16,17,18,19]. The groups that have built BEC based interferometers have mitigated the decoherence by either using a double reflection geometry or using the classical turning points of the residual potential to reflect the atoms.…”
Section: Introductionmentioning
confidence: 99%